1988
DOI: 10.1007/bf00024908
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aquatic macrophytes on phosphorus cycling in lakes

Abstract: Emergent macrophytes take up their phosphorus exclusively from the sediment. Submerged species obtain phosphorus both from the surrounding water and from the substrate, but under normal pore and lake water phosphorus concentrations, substrate uptake dominates. Release of phosphorus from actively growing macrophytes (both submerged and emergent) is minimal and epiphytes obtain phosphorus mainly from the water. Decaying macrophytes may act as an internal phosphorus source for the lake and add considerable quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
76
0
6

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(87 citation statements)
references
References 92 publications
5
76
0
6
Order By: Relevance
“…Sub-catchments 2 and 3 contributed approximately 21% of the total P load to the wetland, but this input alone can not explain the high amount of P in the upper sediment layer of the shallow vegetated areas. Emergent macrophytes, such as T. latifolia, are able to supply their nutrient demand from the sediments alone, acting as P "pumps" transferring P from the sediment to the aboveground plant tissues (Granéli & Solander, 1988). Though the topsoil had been removed, it is likely that the mineral soil on which the wetland was constructed contained P available to plants as it was formerly agricultural land.…”
Section: Discussionmentioning
confidence: 99%
“…Sub-catchments 2 and 3 contributed approximately 21% of the total P load to the wetland, but this input alone can not explain the high amount of P in the upper sediment layer of the shallow vegetated areas. Emergent macrophytes, such as T. latifolia, are able to supply their nutrient demand from the sediments alone, acting as P "pumps" transferring P from the sediment to the aboveground plant tissues (Granéli & Solander, 1988). Though the topsoil had been removed, it is likely that the mineral soil on which the wetland was constructed contained P available to plants as it was formerly agricultural land.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic is even more pronounced in ecosystems with low nutrient concentrations, such as the clear and black water Amazonian ecosystems (Sioli, 1984;Setaro & Melack, 1984;Esteves et al, 1990). The participation of aquatic macrophytes in nutrient cycling has been verified by many authors (e.g., Granéli & Solander, 1988;Nogueira et al, 1996), who have demonstrated the role of this community in the absorption of nutrients from the sediment as well as their liberation in the water column.…”
Section: Introductionmentioning
confidence: 82%
“…Perez-Llorens & Niell (1989) reported a foliar release in Z. no/Iii of 0.05/Lmol P·g-I·h -I (7.1 mg P-m -2·day-l) in an in situ experiment. Graneli & Solander (1988), in a review paper, supported the idea that the P released to the water from actively growing macrophytes is, in general, low, reporting rates of 0.01-0.03/Lmol P'g-l'h -I, which are in agreement with the values found in Z. no/Iii: 0.014 }lmol P'g-I'h -I in the dark (2% of the P taken up) and 0.025/Lmol P'g-l'h -1 in the light (4%).…”
Section: Discussionmentioning
confidence: 99%
“…noitii, as others submerged aquatic angiosperms, is capable of taking up P from the surrounding water by the leaves as well as by the root-rhizomes from the interstitial water of the sediment. Presumably, the sediment is the principal source of phosphate but the relative concentrations of phosphate in the water and sediment determine the main site for uptake (McRoy & Barsdate, 1970;Bristow & Whitecombe, 1971;Denny, 1972;McRoy et aL, 1972;Patriquin, 1972;DeMarte & Hartman, 1974;Gentner, 1977;McRoy & McMillan, 1977;Twilley et al, 1977;Best & Mantai, 1978;Carignan & Kalff, 1979;Welsh & Denny, 1979;Penhale & Thayer, 1980;Carignan, 1982;Gabrielson et aL, 1984;Brix & Lingby, 1985;Smith & Adams, 1986;Graneli & Solander, 1988;Moeller et al, 1988).…”
Section: Introductionmentioning
confidence: 99%